Personal Branding Melalui Media Sosial Dalam Meningkatkan Community Awareness Terhadap Isu Lingkungan - Moh Sakir (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The purpose of this study is to; identify effective personal branding strategies on social media, assess the impact of personal branding in increasing community awareness, and provide practical recommendations for individuals and organizations in building personal branding. Social media has become a major catalyst in connecting individuals and communities in the digital era. Personal branding, which is essentially an effort to build a consistent self-image, can be used strategically to increase community awareness on important issues. This article explores how social media can be utilized to build authentic personal branding, and examines its impact in expanding the reach of social messages. Through a literature review and case studies, this article provides practical guidance for individuals who want to maximize the role of social media in mobilizing communities.